(untitled) (Journal of Humanities and Social Sciences Research, 2022)
The importance of the research is crystallized in the effect of using an educational program in learning the effectiveness of free swimming for students. The problem of the research lies in the weakness in the speed of learning and mastery of free swimming among students, and from here came the researcher the idea of ​​learning free swimming for students using auxiliary tools The educational program, that the good use of auxiliary tools contributes to A significant limit in the student’s ability to learn speed, master the skill of swimming, reduce the degree of fear of water, feel calm and increase self-confidence, and it helps in shortening the time allocated to learning the effectiveness of free swimming. The research aims to identify the effect of using an educational program with tools to help learn the effectiveness of free swimming. For students, and to identify the effect of the educational program with tools in learning the effectiveness of free swimming for students, as for the research hypotheses, there is an effect in the use of the educational program with tools to learn the effectiveness of free swimming for students The researcher used the experimental method by designing the two equal groups (experimental and control) with a pre and post test as it fits with the nature of the research problem. The research community included the students of the first stage - Department of Physical Education and Sports Sciences - College of the Future University, which numbered (200) students, and students were also excluded those who can swim, numbering (140) students, as well as students absent from taking tests and measurements and their number (30), as well as the exclusion of the students participating in the two exploratory experiments and their number (10) students, bringing the number of the sample to (20) students, and thus the sample constitutes (45%) ) from the original community, and they were divided equally into two groups, and for each group (10) students, they were divided into two control and experimental groups using a lottery. The educational program was applied on (2/3/2022) for a period of six weeks with two educational units per week on (Saturdays and Wednesdays). The educational units included (4) skills that are among the basic skills in learning the effectiveness of free swimming, which are (flow with the movement of the legs, breathing, flow with the movement of the arms, free swimming in full). After completing the educational units, the data was processed using the (spss) system. The effect of using an educational program with auxiliary tools in reducing psychological stress is better than the program followed by the teaching staff. Positive effect in reducing the level of psychological stress, and one of the most important recommendations is the need to learn the effectiveness of free swimming for its contribution to reducing the level of psychological stress, the need to use auxiliary tools continuously and according to the stage of learning the effectiveness of free swimming, not to allow the learner to practice swimming while he is in a poor psychological state